The Relationship between Working Capital Management and Profitability: A Case Study of Cement Industry in Pakistan - Haq, Ikram ul; Sohail, Muhammad; Zaman, Khalid; Alam, Zaheer (Richtmann Publishing, 2011)
This study empirically examines the relationship between working capital management and profitability by using data offourteen companies in cement industry in the Khyber Pakhtonkhuwa Province (KPK) of Pakistan. The study is based on secondary datacollected from financial reports which is listed in Karachi Stock Exchange for the period of six years from 2004-2009. The data wasanalyzed using the techniques of correlation coefficient and multiple regression analysis. All the findings were tested at 0.01 and 0.05level of significance. The result concludes that there is a moderate relationship between working capital management and profitability inthe specific context of cement industry in Pakistan.